Validation and Improvements of a Generalized/eXtended Finite Element Method for 3-D Fatigue Crack Propagation - Avecillas-Leon, Javier A.; Singh, Ishank; Duarte, C. Armando (International journal of fracture, 2025)
The main objectives of this paper are to simulate 3-D fatigue crack propagation using a Generalized Finite Element Method (GFEM) and to validate the results against experimental data. This GFEM adopts a high-order p-hierarchical basis and explicit representations of crack surfaces. Both h-refinement around the fracture fronts and non-uniform p-enrichment of the analysis domain are used to control discretization errors. A systematic validation of this GFEM applied to 3-D fatigue crack propagation has not been reported in the literature. The Displacement Correlation Method (DCM) is used to extract stress intensity factors. The effect of material parameters adopted in the DCM on the crack growth rate and fracture shape is investigated. Three increasingly complex fatigue crack propagation problems are solved. The first involves mixed-mode loading in a modified compact tension specimen. The second one involves the transition from 2-D to 1-D crack surfaces and interactions between the crack front and the corners of the domain boundary. The final problem simulates the growth of a circumferential surface crack in a steel pipe subjected to fatigue bending with overloading, where interactions between the crack and the pipe’s inner surface result in the splitting of the crack front. Another contribution is an algorithm designed to manage cyclic load histories featuring variable loading ranges and ratios between minimum and maximum load magnitudes.